British cinema and the Cold War : the state, propaganda and consensus / Tony Shaw. - Shaw, Tony, 1965- (Cinema and society series, 2001)
This text uncovers British cinema's contribution to Cold War propaganda, and its attempts to create a consensus among British audiences on Cold War issues. It examines the Cold War as refracted through the silver screen.